2020
DOI: 10.1101/2020.07.29.20164285
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disease severity dictates SARS-CoV-2-specific neutralizing antibody responses in COVID-19

Abstract: COVID-19 patients exhibit differential disease severity after SARS-CoV-2 infection. It is currently unknown as to the correlation between the magnitude of neutralizing antibody (NAb) responses and the disease severity in COVID-19 patients. In a cohort of 59 recovered patients with disease severity including severe, moderate, mild and asymptomatic, we observed the positive correlation between serum neutralizing capacity and disease severity, in particular, the highest NAb capacity in sera from the patients with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
43
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 31 publications
16
43
2
Order By: Relevance
“…Furthermore, Gene Set Variation Analysis (GSVA) with public gene sets revealed that gene sets related to B cell response and T cell response were predominantly enriched in the aged group (G3) at 2 dpi, compared to the juvenile (G1) or the young adult (G2) ferrets (Fig. 4D), which is in agreement with a recent clinical study that showed stronger antibody and T cell responses in severe COVID-19 patients than mild patients 21,22 . Moreover, other immune-related gene sets, including IFN response, macrophage activation, and NK cell activation, were also highly enriched in the aged group at 2 dpi (Fig.…”
Section: Transcriptional Pro Le Of Immune-related Genes In Lung Tissusupporting
confidence: 90%
“…Furthermore, Gene Set Variation Analysis (GSVA) with public gene sets revealed that gene sets related to B cell response and T cell response were predominantly enriched in the aged group (G3) at 2 dpi, compared to the juvenile (G1) or the young adult (G2) ferrets (Fig. 4D), which is in agreement with a recent clinical study that showed stronger antibody and T cell responses in severe COVID-19 patients than mild patients 21,22 . Moreover, other immune-related gene sets, including IFN response, macrophage activation, and NK cell activation, were also highly enriched in the aged group at 2 dpi (Fig.…”
Section: Transcriptional Pro Le Of Immune-related Genes In Lung Tissusupporting
confidence: 90%
“…perpetuity. preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in The copyright holder for this this version posted February 16, 2021. ; https://doi.org/10.1101/2021.02.12.21251298 doi: medRxiv preprint equivocally related to COVID-19 disease severity (34,35), we investigated their possible prognostic accuracy for overall-mortality at 28 days in ICU patients. ROC curve analyses using continuous biomarker values indicated that the only significant predictor was IgG against the Spike/TLR2 mimic peptide, but only modestly so, with an area under the curve of 0.64.…”
Section: Baseline Serologies and Icu Patients Prognosismentioning
confidence: 99%
“…However, many essential aspects of virus-host interactions during SARS-CoV-2 infection remain unclear, including the production and longevity of virus-specific antibodies in infected persons, and their implications on protection from re-infection. At present, there are conflicting data on the incidence of virus-neutralizing antibodies in asymptomatic and non-severe cases of COVID-19 [8,9]. Given the range of disease severity in humans, it is important to elucidate the similarities and differences between symptomatic and asymptomatic infections of SARS-CoV-2 and their implications for long-term protection, potential re-infections, herd immunity, and treatment options.…”
Section: Introductionmentioning
confidence: 99%